Effectiveness use Interactive Media Applications Sparkol Videosribe on Results Study Social Sciences Student Class VII Junior High School Muhammadiyah Rappang - Nur Fitriani Ilham; Abd. Kahar; Muhammad Takdir; Sam Hermansyah (MultiTech Publisher, 2024)
This influence research aims to determine the The aim of this research is to determine how effective the use of interactive media from the Sparkol Videoscribe application is on the social studies learning performance of students in Class VII SMP Muhammadiyah Rappang. For this research, a one group pretest-posttest and quasi-experimental design was used. This research involved 28 students from class VII.a Muhammadiyah Rappang Middle School. There are two data collection methods used to measure student learning outcomes, namely learning completeness and timeliness in obtaining material. The research results showed that class VII students at SMP Muhammadiyah Rappang achieved good social studies learning outcomes by using the Sparkol Videoscribe application as an interactive medium. The sample test results show this... This is shown from the T-test sample test results of pretest and posttest data on student learning outcomes found mark significance. From results study This Which has analyzed, then obtained mark flat- average M x( Posttest ) = 82.5 > M y( Pretest ) = 59.57. So it can be concluded that this research show exists effectiveness use media interactive Sparkol app Videoscribe to results Study student.